2020
DOI: 10.3390/nu12020292
|View full text |Cite
|
Sign up to set email alerts
|

The Emerging Role of Vitamin C as a Treatment for Sepsis

Abstract: Sepsis, a life-threatening organ dysfunction due to a dysregulated host response to infection, is a leading cause of morbidity and mortality worldwide. Decades of research have failed to identify any specific therapeutic targets outside of antibiotics, infectious source elimination, and supportive care. More recently, vitamin C has emerged as a potential therapeutic agent to treat sepsis. Vitamin C has been shown to be deficient in septic patients and the administration of high dose intravenous as opposed to o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
134
0
28

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(164 citation statements)
references
References 133 publications
(185 reference statements)
2
134
0
28
Order By: Relevance
“…Oleh karena itu, dipikirkan pemberian dosis tinggi vitamin C untuk mengatasi sekuens dari kadar yang suboptimal pada pasien kritis. 114 CITRIS-ALI merupakan studi terbaru yang menilai efektivitas dosis tinggi vitamin C pada sepsis dan gagal napas. Hasil studi menunjukkan tidak terdapat perbedaan antara grup vitamin C dengan dosis 50 mg/kgBB setiap 6 jam selama 96 jam dengan plasebo pada penurunan skor SOFA.…”
Section: Vitamin Cunclassified
“…Oleh karena itu, dipikirkan pemberian dosis tinggi vitamin C untuk mengatasi sekuens dari kadar yang suboptimal pada pasien kritis. 114 CITRIS-ALI merupakan studi terbaru yang menilai efektivitas dosis tinggi vitamin C pada sepsis dan gagal napas. Hasil studi menunjukkan tidak terdapat perbedaan antara grup vitamin C dengan dosis 50 mg/kgBB setiap 6 jam selama 96 jam dengan plasebo pada penurunan skor SOFA.…”
Section: Vitamin Cunclassified
“…Vitamin C reinforces the maintenance of the alveolar epithelial barrier and transcriptionally upregulates the protein channels (CFTR, aquaporin-5, ENaC, and Na+/K+ ATPase) regulating the alveolar fluid clearance [37]. HDIVC has been implicated in reducing plasma cell-free DNA formed from the neutrophil extracellular trap (NET) which is the facilitator of systemic inflammation in sepsis-induced multi-organ failure [38,39]. Interestingly, elevated levels of syndecan-1 in the plasma correlate with increased mortality in severe sepsis and ARDS, and this endothelial glycocalyx can be reduced significantly by HDIVC [39].…”
Section: Role Of Vitaminsmentioning
confidence: 99%
“…HDIVC has been implicated in reducing plasma cell-free DNA formed from the neutrophil extracellular trap (NET) which is the facilitator of systemic inflammation in sepsis-induced multi-organ failure [38,39]. Interestingly, elevated levels of syndecan-1 in the plasma correlate with increased mortality in severe sepsis and ARDS, and this endothelial glycocalyx can be reduced significantly by HDIVC [39]. As of 14 February 2020, there is a randomized controlled trial (RCT) undertaken at the Zhongnan Hospital (NCT04264533) that aims to evaluate the clinical efficacy and safety of vitamin C in viral pneumonia from SARS-CoV-2.…”
Section: Role Of Vitaminsmentioning
confidence: 99%
“…In a randomised, crossover, controlled study, vitamin C supplement of 1000 mg twice a day increased urinary oxalate in 40% of the participants, which in turn increases the risk of oxalate kidney stone [ 103 ]. Interestingly, in sepsis clinical trials, no series adverse effects, including kidney stones, have been reported to date [ 104 ]. This can be explained by the fact that vitamin C is water soluble, therefore, intoxication due to excessive intake of vitamin C is unlikely as the concentration of vitamin C which exceeds the body daily requirement will be excreted by the kidneys [ 47 ].…”
Section: The Safety Profile Of Vitamin Cmentioning
confidence: 99%
“…Treatment with high dose of vitamin C might interfere with the accuracy of the glucometer measurement of blood glucose level, as both vitamin C and Glucose have similar molecular structure, which could lead to false high blood glucose readings, and the diagnosis of clinically significant hypoglycaemia can be easily missed [ 105 , 106 ]. Therefore, clinicians should rely on laboratory blood samples or venous blood gases for measurement of blood glucose in patients treated with high dose of vitamin C to avoid missing the diagnosis of hypoglycaemia or increasing the risk of hypoglycaemia caused by unnecessary insulin treatment based on inaccurate glucometer readings [ 104 ]. A dose adjustment of vitamin C might be required in patients with renal impairment [ 107 ].…”
Section: The Safety Profile Of Vitamin Cmentioning
confidence: 99%